Muhammad Bin Abdul Wahab's Thoughts About Monotheistic Education - Astuti, Sri Dewi (Jurnal Ilmiah Mandala Education (JIME), 2024)
Education is very important in the life of every human being. With human education, children, even people are able to develop and have good potential. Therefore, it is important to learn calm tawhid, especially in this discussion of Muhammad bin Abdul Wahhab. The basis of tawhid education is an effort in Islamic education, because with this tawhid education is nothing but an Islamic outlook on life. This research uses qualitative methods, with data collection techniques using library research, where researchers use several library sources as references in this study. The sources used come from journals accessed through Google Scholar using the keywords, Tawhid education, the purpose of Tawhid education, then the data is analyzed and conclusions are drawn to answer research questions.